Optimization of Outpatient Waiting Times to Improve the Achievements of National Quality Indicators at TNI AD 05.08.04 Hospital Lawang - Wieko Prayudi; Ganista Alkautsar; Ika Retnani; Titis Ari Respatilatsih; Indasah (Universitas STRADA Indonesia, 2024)
The waiting time for outpatient services in a hospital is one of the important factors determining patient satisfaction with the hospital, so it is hoped that patients will not wait too long while in the hospital. This study aimed to optimize outpatient waiting times so that it can increase the achievement of national quality indicators at TNI AD 05.08.04 Hospital, Lawang. This study used fishbone diagrams, USG (Urgency, Seriousness, Growth), and SWOT Analysis (Strength, Weakness, Opportunity, Treats) to formulate problems and find solutions. The results of this study showed that priority problems in waiting time include: standard operating procedure (SOP) for outpatient service flow are still not available, the electronic medical record system is still often slow, and evaluation of national quality indicators is still not carried out routinely. Furthermore, the proposed strategy offered is the creation of SOP regarding the flow of outpatient services and routine outreach regarding the use of electronic medical records. With the implementation of these two strategies, it is hoped that they will be able to speed up waiting times for outpatient services, thus improving the achievement of national quality indicators.